Development of guideline for building defects : case study- shopping mall - Nur Farah Huda, Mohd Zaimi @ Mohd Zalmi (2019)
This study was conducted to investigate the building defects and problems associate with building maintenance in commercial buildings especially shopping mall centers. The main objective of the study is to identify building defects, analyze people awareness and perspectives on defects problems and develop a defects maintenance guideline for shopping mall building. The method used to conduct this study are observation, questionnaire survey and interview session. Observation of shopping mall conducted to identify defects exist and sets of question form is used to identify and analyze the level of public awareness and perspective towards building defects problem. Interview session held with three respondents which are Professional Engineers and Operation Manager that expert in managing building maintenance matters to gain more information related to this research.